Microalgae as a Source of Valuable Phenolic Compounds and Carotenoids - Jan Cichoński; Grzegorz Chrzanowski (Molecules, 2022)
Microalgae are photosynthetic, eukaryotic organisms that are widely used in the industry as cell factories to produce valuable substances, such as fatty acids (polyunsaturated fatty acids (PUFAs) eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA)), sterols (sitosterol), recombinant therapeutic proteins, carbohydrates, vitamins, phenolic compounds (gallic acid, quercetin), and pigments (β-carotene, astaxanthin, lutein). Phenolic compounds and carotenoids, including those extracted from microalgae, possess beneficial bioactivities such as antioxidant capacity, antimicrobial and immunomodulatory activities, and direct health-promoting effects, which may alleviate oxidative stress and age-related diseases, including cardiovascular diseases or diabetes. The production of valuable microalgal metabolites can be modified by using abiotic stressors, such as light, salinity, nutrient availability, and xenobiotics (for instance, phytohormones).